PSIAPP: THERAPEUTIC SESSION MANAGEMENT SYSTEM (CIPEEX, 2024)
SIMPLE SUMMARY PRESENTED WITH THE AIM OF PROVIDING INFORMATION ABOUT THE PSIAPP APPLICATION, A PLATFORM FOR PSYCHOLOGISTS AND PATIENTS TO MANAGE THEIR THERAPY SESSION SCHEDULES.
Keywords: Psychology; Mental health; Technology; Psychologists